Donor-Derived Transmission Events in 2013: A Report of the Organ Procurement Transplant Network Ad Hoc Disease Transmission Advisory Committee. Issue 2 (February 2015) - Green, Michael; Covington, Shandie; Taranto, Sarah; Wolfe, Cameron; Bell, Walter; Biggins, Scott W.; Conti, David; DeStefano, G. David; Dominguez, Edward; Ennis, Donna; Gross, Thomas; Klassen-Fischer, Mary; et al.
Abstract : Background: The Organ Procurement Transplant Network Disease Transmission Advisory Committee (DTAC), a multidisciplinary committee, evaluates potential donor-derived transmission events (PDDTE), including infections and malignancies, to assess for donor transmitted events. Methods: Reports of unexpected PDDTE to Organ Procurement Transplant Network in 2013 were fully reviewed by DTAC. A standardized algorithm was used to assess each PDDTE from a given donor and to classify each individual recipient from that donor. Results: Of 443 total PDDTE submitted, 159 were triaged and not sent out to the full DTAC. Of 284 fully evaluated reports, 32 (11.3%) resulted in a proven/probable (P/P) transmission of infection, malignancy or other conditions to 42 recipients. Of 204 infection events, 24 were classified as P/P affecting 30 recipients, with four deaths. Bacteria were the most frequently reported type of infection, accounting for 99 reports but only 12 recipients from 11 donors experienced P/P transmission. There were 65 donors reported with potential malignancy events and 5 were classified as P/P transmissions with 8 affected recipients and 2 deaths. Additionally, there were 16 noninfection, nonmalignancy reports resulting in 3 P/P transmissions to 4 recipients and 1 death. Conclusions: There was a 43% increase in the number of PDDTE reported and reviewed in 2013 over 2012. However, the percent with P/P transmission remains low, affecting recipients from 32 donors especially when compared with the more than 14, 000 donors recovered annually in the United States. The continued use of the new standard algorithm and triaging process will enhance the reproducibility of DTAC assessments and allow more robust analysis of our aggregate DTAC experience. Abstract : The Organ Procurement and Transportation Network Disease Transmission Advisory Committee reports on assessment of potential donor-derived transmission events. Infection, malignancy and other causes are evaluated to ascertain the likelihood or not of transmissible events.